Forecasting Seasonal Time Series Data Using The Holt-Winters Exponential Smoothing Method of Additive Models - Nurhamidah Nurhamidah; Nusyirwan Nusyirwan; Ahmad Faisol (Jurnal Matematika Integratif, 2020)
The purpose of this study was to predict seasonal time series data using the Holt-Winters exponential smoothing additive model.  The data used in this study is data on the number of passengers departing at Hasanudin Airport in 2009-2019, the source of the data obtained from the official website of the Central Statistics Agency.  The results showed that the Holt-Winters exponential smoothing method on the passenger's number at Hasanudin Airport in 2009 to 2019 contained trend patterns and seasonal patterns, by first determining the initial values and smoothing parameters that could minimize forecasting errors.